The importance of physical activity in colorectal cancer prevention - Nataša Antoljak (Libri Oncologici, 2020)
Colorectal cancer is the second most common malignant neoplasm and the second cause of death from malignancies in both sexes. In 2017, 3689 people were diagnosed in the Republic of Croatia. Two thousand ninety-five people died of colorectal cancer in 2019. Colorectal cancer is preventable, and it appears that smoking and obesity are factors that affect its onset. Physical inactivity is closely related to obesity, and the question is whether it can be an independent predictor of colon cancer. We searched the literature on Pubmed for the past five years, including systematic reviews and meta-analyses on the association between physical activity and colon cancer incidence. Studies are methodologically diverse and involve different approaches. In most observational studies, greater physical activity is associated with a lower incidence of colon cancer, while in the interventional studies, results were more diverse. In general, smoking tobacco products has a much greater effect on colon cancer development, but physical activity is linked to the onset of the disease and should be one of the prevention measures.